2011
DOI: 10.1371/journal.pone.0028946
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Dopamine Receptors in Binge Methamphetamine-Induced Activation of Endoplasmic Reticulum and Mitochondrial Stress Pathways

Abstract: Single large doses of methamphetamine (METH) cause endoplasmic reticulum (ER) stress and mitochondrial dysfunctions in rodent striata. The dopamine D1 receptor appears to be involved in these METH-mediated stresses. The purpose of this study was to investigate if dopamine D1 and D2 receptors are involved in ER and mitochondrial stresses caused by single-day METH binges in the rat striatum. Male Sprague-Dawley rats received 4 injections of 10 mg/kg of METH alone or in combination with a putative D1 or D2 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 75 publications
(138 reference statements)
4
72
0
Order By: Relevance
“…9,23 Additionally, this binge protocol has been widely used in animal studies and is well characterized by striatal toxicity. 42 However, little is known about the effect of this METH regimen on BBB function. Nevertheless, Urrutia et al 10 showed that a similar METH binge protocol (3 × 4 mg/kg) induced BBB disruption in mouse striatum at 1, 12, and 24 hours after METH treatment, observed by extravasation of Immunoglobulin G (150 kDa).…”
Section: Discussionmentioning
confidence: 99%
“…9,23 Additionally, this binge protocol has been widely used in animal studies and is well characterized by striatal toxicity. 42 However, little is known about the effect of this METH regimen on BBB function. Nevertheless, Urrutia et al 10 showed that a similar METH binge protocol (3 × 4 mg/kg) induced BBB disruption in mouse striatum at 1, 12, and 24 hours after METH treatment, observed by extravasation of Immunoglobulin G (150 kDa).…”
Section: Discussionmentioning
confidence: 99%
“…This was an expected result, as METH neurotoxicity occurs after regimens that result in a relatively long presence of METH in the brain, such as multiple injections of the drug (4 × 5–10 mg/kg) or a massive single dose of METH (30–60 mg/kg) [11]. Binge and massive single doses of METH induce hyperthermia that lasts longer than 4 h [40,41]; therefore, our data suggest that short-lasting hyperthermia does not lead to neurotoxicity to DAergic terminals.…”
Section: Resultsmentioning
confidence: 99%
“…At the molecular level, D 1 -like receptors blockade decreasesDA-induced oxidation and cytotoxicity mediatedby the activation of extracellular-signalregulated kinase (ERK) and c-Jun N-terminal kinases (JNK) (Chen et al, 2004). In addition,SCH-23390 completely blocked METH-induced expression of endoplasmic reticulum stress-related proteins (ATF3, ATF4, CHOP/Gadd153, HSPs and caspase 12), inhibitedMETH-induced increase in pro-survival genes in response to endoplasmic reticulum stress (includingBIP/GRP-78 and P58IPK) and increased expression of the mitochondrial anti-apoptotic protein Bcl-2 in the striatum (Beauvais et al, 2011). However, as SCH-23390 does not distinguish between D 1 andD 5 receptors (Moratalla et al, 1996b) and, as mentioned above, interacs with 5-HT receptors (Kvernmo et al, 2006), it was not clear exactly which receptor subtypes were involved in METH-induced neurotoxicity.…”
Section: 3role Of Da Receptors: D 1 Receptors In Meth-induced Neumentioning
confidence: 99%